Media and Violence: Violence in Media or Violent Media - Glomazić, Hajdana; Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
The purposeless showing of violence in the media is a social problem. It has to be considered in terms of inventing efficient mechanisms of protection from media violence, based on an analysis of its origins and effects. An analytical approach to this problem offers insight into the ways it is possible to avoid its negative consequences to individuals and society as a whole. The subject of this paper is the analysis of the phenomenon of media violence, and its goal is to provide an answer to the question of its effects at various social levels (individual, social). Results of the analysis have shown that, regardless of the data obtained by empirical research, there is no general consensus with regard to the degree to which violent content in the media presents a factor of future violent behaviour. Still, the authors agree that long-term exposure to media violence has negative consequences in the physical, mental and ethical sense, and also on stabilization of a violent person, especially with regard to young people.